(untitled) (Journal of Coating Science and Technology, 2017)
Osteoblast viability, proliferation, protein expression and mineralization were studied on bare, micro- and nanoporous silicon (Si) substrates. Micro- and nano-porous-Si substrates were prepared by anodic etching of silicon in ethanolic hydrofluoric acid and characterized using scanning electron and atomic force microscopies. Mouse osteoblasts were cultured on these substrates and cellular response to these surfaces was assessed using the Live/Dead Cell Viability assay and the MTT assay for cell proliferation. Osteoblast functionality was assessed using immunohistochemistry for bone protein specific markers. Osteoblasts grew well on micro- and nanoporous silicon substrates over the twenty-one day experimental period supporting the assessment that these are suitable cell supportive surfaces. Cell proliferation rates on bare and nanoporous silicon were similar initially, however, nanoporous silicon displayed enhanced cell proliferation, in comparison to bare silicon, after 14 days in culture. Immunocytochemical assays, using bone specific markers, showed positive reactions for osteonectin and osteopontin expression on all substrates with staining intensity increasing over the 21-day experimental period. Calcium mineral deposits were quantified using the Alizarin Red histochemical assay and nanoporous silicon induced the highest level of calcium mineral production in comparison to bare and microporous silicon. The data supports the potential use of nanoporous silicon as a surface implant coating for dental and orthopedic applications. The ability to dope (and then release) drugs or growth factors from the silicon nanopores offers the potential for a multi-functional implant surface.